Inhibitory effect of caveolin-1 in vascular endothelial cells, pericytes and smooth muscle cells - Xu, Hongping (Oncotarget, 2017)
Caveolin-1 (Cav1) is the principle structural protein of caveolae. It plays important roles in the vascular system under both physiological and pathological conditions. Although Cav1 has been shown to inhibit microvascular permeability and has been considered as a tumor-suppressor for years, the underlying cellular mechanism has yet to be discovered. Here, we systematically investigated Cav1 functions in the main types of vascular cells, including endothelial cells (ECs), pericytes (PCs) and smooth muscle cells (SMCs). We synthesized a cell-permeable peptide called cavtratin that is derived from the Cav1 scaffolding domain. We found that cavtratin inhibited ECs in all assays, including survival, proliferation, migration and permeability assays. It also inhibited the proliferation of PCs and SMCs but had no effect on their survival or migration. The inhibitory effect of cavtratin on the proliferation of all vascular cells suggests that Cav1 plays important roles in vascular development and angiogenesis. Under physiological condition, the main function of Cav1 is to inhibit EC permeability.